Analisis Qaidah الضر ار يز ال Serta Bagaimana Penerapannya Dalam Kehidupan Sehari-Hari - Muh. Zamroni; Azizah Nuzulan Sahuurab; M. Shoim Maulidi; Aulia Rosferyn Mufidah P.J (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
The Islamic legal "Ad-Dhararu Yuzal" (الضرر يزال), meaning "harm must be eliminated," represents one of the fundamental principles in Islamic law. However, practical implementation of this maxim still faces various challenges, ranging from varying levels of public understanding to difficulties in application. This study aims to analyze the effectiveness of implementing the maxim "Ad-Dhararu Yuzal" in contemporary problem-solving, identify factors influencing successful implementation, and formulate an optimal implementation model to enhance the quality of Sharia-based. Research findings indicate that public understanding of the "Ad-Dhararu Yuzal" maxim falls within the moderate category. Multiple regression analysis reveals that maxim understanding, socialization intensity, and religious educational background simultaneously of the variance in problem-solving effectiveness. Qualitative analysis identified five main themes: gradual understanding of harm hierarchy, maxim adaptability to local contexts, integration with other fiqh maxims, religious leaders' role as implementation mediators, and application challenges in modern ethical dilemmas. The "Ad-Dhararu Yuzal" maxim proves effective as a decision-making framework in contemporary problem contexts, provided adequate understanding exists alongside structured socialization support systems. The optimal implementation comprises three main components: tiered education programs tailored to target audiences, mentoring systems by competent religious figures, and continuous evaluation mechanisms.